Potential Role of HMGCS2 in Tumor Angiogenesis in Colorectal Cancer and Its Potential Use as a Diagnostic Marker. (1st July 2019) - Zou, Kejian; Hu, Yan; Li, Musheng; Wang, Hongli; Zhang, Yuhua; Huang, Ling; Xie, Yuanwen; Li, Songyu; Dai, Xingui; Xu, Wanfu; Ke, Zhiyong; Gong, Sitang; et al.
Abstract : Objective . HMGCS2 is the rate-limiting enzyme of ketogenesis, which is vital for tumor initiation or metastasis. The aim of this study is to determine the relationship between HMGCS2 and tumor angiogenesis. Materials and Methods . The study consisted of 100 cases with colorectal cancer and healthy control, the expression of HMGCS2 and the microvessel density (MVD) (marker: CD31) were analyzed by immunohistochemistry and tube formation, and the centration of β -hydroxybutyrate in serum was assessed by biochemical analysis. Results . The results showed that HMGCS2 expression is significantly reduced in colorectal cancer compared with healthy control, which is inversely correlated with MVD in colorectal cancer by IHC analysis. What is more, knockdown HMGCS2 expression in HT-29 cells significantly contributed endothelial cell tube formation. Conclusion . These findings implying HMGCS2 may have a negative regulation of tumor angiogenesis and provide an approach to inhibit tumor angiogenesis.